Isolation and characterization of Bacillus thuringiensis strains active against Elasmopalpus lignosellus (Zeller, 1848) (Lepidoptera, Pyralidae) - Zorzetti, Janaina; Ricietto, Ana Paula Scaramal; Fazion, Fernanda Aparecida Pires; Meneguim, Ana Maria; Neves, Pedro Manuel Oliveira Janeiro; Vilas-Bôas, Gislayne Trindade (Acta Scientiarum. Agronomy, 2017)
Elasmopalpus lignosellus (Zeller, 1848) (Lepidoptera, Pyralidae) is an insect pest of 60 economically important crops, including sugarcane, wheat, soybean, rice, beans, sorghum, peanuts, and cotton. The aim of this work was to select and characterize Bacillus thuringiensis isolates with insecticidal activity against E. Lignosellus that could be used as an alternative method of control. Selective bioassays were done to evaluate the toxicity of 47 isolates against first instar larvae of E. lignosellus. For the most toxic bacterial strains, the lethal concentration (LC50) was estimated and morphological, biochemical and molecular methods were used to characterize the isolates. Among the 47 isolates tested, 12 caused mortality above 85% and showed LC50 values from 0.038E+8 to 0.855E+8 spores mL-1. Isolates BR83, BR145, BR09, BR78, S1534, and S1302 had the lowest LC50 values and did not differ from the standard HD-1 strain; the exception was BR83.The protein profiles produced bands with molecular masses of 60-130 kDa. The genes cry1, cry2, cry3, and cry11 were identified in the molecular characterization. The morphological analysis identified three different crystal inclusions: bipyramidal, spherical and cuboidal. Among the tested isolates, 12 isolates have potential for biotechnological control of E. Lignosellus by development of new biopesticides or genetically modified plants.